2020
DOI: 10.1177/1940844720939847
|View full text |Cite
|
Sign up to set email alerts
|

Bloggers on FIRE Performing Identity and Building Community: Considerations for Cyber-Autoethnography

Abstract: As a research approach, autoethnography has revolutionized qualitative inquiry. To date, most autoethnographies represent the lives of academics and are published in the research press for a small audience of other academics. However, in the digital world, a subset of blogs has emerged in which the self-narratives are substantially similar to autoethnographies in content, quality, and level of social commentary, but with a broader scope and audience. For example, FIRE bloggers write about how they are striving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
(13 reference statements)
0
6
1
Order By: Relevance
“…Loss or perceived potential loss of these two resources may affect consumers’ attitude and behavior toward the adoption of FIRE. While prior studies on FIRE or financial independence showed individuals’ desire to retire early from paid work to follow their passion or pursue more meaningful work (Lapadat, 2020; Perrone et al , 2015), this study shows that participants also experience motivation to adopt FIRE goals to recover their health and well-being resources. The boundary conditions such as individual competencies (DIY attitude, ability to live frugally, planning and execution ability), a well-paying job and support from one’s spouse strengthens, while the resistance from social groups weakens FIRE adoption motivations.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…Loss or perceived potential loss of these two resources may affect consumers’ attitude and behavior toward the adoption of FIRE. While prior studies on FIRE or financial independence showed individuals’ desire to retire early from paid work to follow their passion or pursue more meaningful work (Lapadat, 2020; Perrone et al , 2015), this study shows that participants also experience motivation to adopt FIRE goals to recover their health and well-being resources. The boundary conditions such as individual competencies (DIY attitude, ability to live frugally, planning and execution ability), a well-paying job and support from one’s spouse strengthens, while the resistance from social groups weakens FIRE adoption motivations.…”
Section: Discussioncontrasting
confidence: 59%
“…We developed a conceptual model from these findings, as shown in Figure 1. Second, while prior studies mainly focused on FIRE experts and pioneers in developed economies (Lapadat, 2020; Taylor and Davies, 2021), this study explored general consumers’ FIRE behavior in an emerging economy context. Third, this study is one of the first to apply COR theory to understand consumer motivations for FIRE goals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations